2019
DOI: 10.14744/anatoljcardiol.2019.00905
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blood Pressure Variability on Hypertensive Patients’ Prognosis

Abstract: Objective:Our study aims to compare the effects of blood pressure variability (BPV) during ambulatory blood pressure measurement (ABPM) and visit-to-visit measurements to predict future cardiovascular complications among hypertensive patients.Methods:This is a retrospective case-control study of patients with hypertension over 10 years. All adult patients with at least one recorded ABPM, and at least three recorded visit measurements were included. Patients with incomplete ABPM readings, a history of a tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In the present study, we determined that children with OSA had increased SBP variability during the nighttime. This finding was consistent with those of studies on adults 22,50,51 . Future studies should further investigate the relationship between BP variability and other cardiovascular outcomes in children with OSA.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, we determined that children with OSA had increased SBP variability during the nighttime. This finding was consistent with those of studies on adults 22,50,51 . Future studies should further investigate the relationship between BP variability and other cardiovascular outcomes in children with OSA.…”
Section: Discussionsupporting
confidence: 91%
“…Another method to assess BP variability in 24‐hour ambulatory BP monitoring is using the standard deviation of BP measurements 22,50,51 . Studies by Steinhorst et al 50 and Martynowicz et al 22 reported similar findings that OSA increased nighttime BP variability in adult patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations